English Language Educators? Motivational Strategies: Towards Career Advancement - Chong S.T.; Rahman A.Z.A.; Arjanto P. (Springer Science and Business Media Deutschland GmbH, 2025)
This paper seeks to explore the motivational strategies employed by Malaysians English language educators to teach and learn the newly reformed English language syllabus. The new syllabus is aligned with the Common European Framework of Reference for Languages (CEFR). This is due to the fact that educators who have yet to achieve the required CEFR levels are facing issues especially related to their career advancement. The methodology used is interpretative phenomenological analysis (IPA). Data were fathered through intensive interviews. In this paper, the researchers only discussed data collected from three educators. The findings indicate that Malaysian English language educators are very positive about the new syllabus and are eager to reskill and upskill themselves. They used a variety of motivational strategies to achieve their goals. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.